Developing a support model for hybrid work-integrated continuous professional development - Marcia Håkansson Lindqvist; Peter Mozelius; Jimmy Jaldemark (Springer, 2024)
Abstract In the contemporary digitalised knowledge society, work-integrated professional development is an important and continuous activity. Continuous professional development should preferably be a hybrid format, where academia collaborates with industry and the surrounding society in a multi-directed exchange of ideas. Continuous professional development is today conducted in a blend of workplace activities, and in technology enhanced online environments. A complex blend for professionals that at the same time are working full-time with their ordinary jobs. The need for a support model to navigate in these new digital learning spaces is obvious, where the support model also should include collaboration and a community of practice. A community where the members communicate regularly to improve their skills and knowledge in their common professional domain. The aim of this paper is to describe and analyse the development of a support model that involves these aspects. Findings confirm the necessity of the four steps in the earlier model, at the same time as they indicate the need for a fifth step facilitating the creation of Communities and Landscapes of Practice. The use of the model may support higher education institutions in creating beneficial conditions for hybrid work-integrated continuous professional development for industry.